Less Than Total Excision of Infected Prosthetic PTFE Graft Does Not Increase the Risk of Reinfection. (January 2015) - Sgroi, Michael D.; Kirkpatrick, Vincent E.; Resnick, Karen A.; Williams, Russell A.; Wilson, Samuel E.; Gordon, Ian L.
Background: Traditional treatment of infected polytetrafluoroethylene (PTFE) grafts consist of removal of the entire prosthesis. Closure of the native vessels may compromise vascular patency. We examined the outcomes for patients in whom a PTFE remnant of an infected graft was retained on the vessel. Methods: We reviewed the operating room log from 2000 to 2011 and identified all patients who had partial removal of an infected PTFE graft used for hemodialysis or peripheral bypass. These patients were examined for subsequent complications. Results: Twenty-seven patients underwent 30 partial graft excisions with mean follow-up of 27 months. A total of 17% (5 of 30) of the partial graft resection procedures resulted in complications. Of 48 total remnants left behind at the arterial or venous anastomoses, reinfection occurred in 15%. Conclusions: Leaving a well-incorporated small 1-to 5-mm PTFE remnant at the arterial or venous anastomoses can be performed safely with a low risk of complications.